Left Ventricular Pseudoaneurysm after Valve Replacement - Lee, Jun Ho (Korean J Thorac Cardiovasc Surg, 2015)
We present a case of left ventricular pseudoaneurysm, which is a very rare and fatal complication of cardiac procedures such as mitral valve replacement. A 55-year-old woman presented to the Department of Thoracic and Cardiovascular Surgery at Hanyang University Seoul Hospital with chest pain. Ten years prior, the patient had undergone double valve replacement due to aortic regurgitation and mitral steno-insufficiency. Surgical repair was successfully performed using a prosthetic pericardial patch via a left lateral thoracotomy.